WorldFish activities on AMU/AMR in aquaculture - Khor, Laura (WorldFish, 2024)
This presentation provides an overview of WorldFish's efforts to tackle AMU and AMR in aquaculture, focusing on its global initiatives, including work in Bangladesh. It describes capacity-building activities like training on bacteriological sampling, developing survey tools, and creating learning resources such as an aquamedicines photobook for AMU referencing. The presentation emphasizes multi-sectoral collaboration under the One Health Initiative, highlighting the development of biosecurity modules, participatory modeling approaches, and advanced diagnostic protocols. It also showcases WorldFish's partnerships and its work on behavior change among value chain actors to reduce AMR risks in aquatic food systems​.